2021
DOI: 10.1002/jcop.22657
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the psychiatric factors that determine the fear of COVID‐19 in healthcare workers and hospital staff in a university hospital in Turkey

Abstract: To examine the association of health and hospital workers' fears of coronavirus disease 2019 (COVID‐19) with anxiety, anxiety sensitivity, depression, and sociodemographic variables during the COVID‐19 pandemic. A total of 527 participants (237 men/289 women) were included, 222 of the participants were doctors, 99 nurses, 22 assistant health personnel, and 182 hospital personnel without health education. Participants filled in the sociodemographic data form, Beck Depression Inventory, Beck Anxiety Inventory, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“… Collectivism Kaçoğlu et al, 2021 176 12 Turkey Europe University students 22.6 Collectivism Kakodkar et al, 2021 198 4.5 India Asia University students N.A. Collectivism Karadem et al, 2021 527 N.A. Turkey Europe Hospital staff 35.7 Collectivism Karahan et al, 2021 138 12.5 Turkey Europe Hospital staff 37.6 Collectivism Kardaş, 2021 679 9 Turkey Europe General population 26.7 Collectivism Krägeloh et al, 2021 1029 4.5 Saudi Arabia Middle East General population 33.7 Collectivism Landa-Blanco et al, 2021 595 N.A.…”
Section: Resultsmentioning
confidence: 99%
“… Collectivism Kaçoğlu et al, 2021 176 12 Turkey Europe University students 22.6 Collectivism Kakodkar et al, 2021 198 4.5 India Asia University students N.A. Collectivism Karadem et al, 2021 527 N.A. Turkey Europe Hospital staff 35.7 Collectivism Karahan et al, 2021 138 12.5 Turkey Europe Hospital staff 37.6 Collectivism Kardaş, 2021 679 9 Turkey Europe General population 26.7 Collectivism Krägeloh et al, 2021 1029 4.5 Saudi Arabia Middle East General population 33.7 Collectivism Landa-Blanco et al, 2021 595 N.A.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding habituation, our data highlight that since pandemic anxiety reduce throughout time, individuals might need additional motivational strategies to continuously engage in preventive behaviors ( Iorga et al, 2021 ; Scrima et al, 2022 ). On the other hand, considering that pandemic anxiety is associated with mental suffering ( Karadem et al, 2021 ), assessing intolerance of uncertainty, the fear about others being infected by COVID-19, and the fear of having the mental health impacted by COVID-19 may be crucial for treating mental health suffering in the pandemic scenario. Also, vaccination may be a factor associated with the reduction of the fear about others being infected since it seemed to reduce as vaccination has advanced in the country lacking its importance in the last two months analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of the pandemic had an essential impact on mental health, precipitating symptoms' onset and lasting more than the SARS-CoV-2 virus itself ( Ornell et al, 2020 ; Taquet et al, 2021 ). The COVID-19 anxiety is one of the cognitive and emotional process responsible for this impact, associated with psychological distress, anxiety, and depressive symptoms ( Karadem et al, 2021 ). On the other hand, COVID-19 anxiety is associated with mitigation behaviors and intention to get vaccinated ( Iorga et al, 2021 ; Scrima et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies focused on the role of anxiety sensitivity in terms of mental health and COVID-19 anxiety and fear. In a cross-sectional study focused on healthcare personnel (e.g., doctors, nurses; n = 527) in Turkey during the pandemic, scholars found the anxiety sensitivity physical concerns to be significantly related to fear of COVID-19; effects larger than that observed for anxiety or depressive symptoms as predictors ( Karadem, Demirdaş, Işık, & Kılıç, 2021 ). In a cross-sectional investigation of 438 university students in the United States (U.S.), Ojalehto, Abramowitz, Hellberg, Butcher, and Buchholz (2021) found that anxiety sensitivity physical concerns were associated with more intense COVID-19 anxiety.…”
Section: Narrative Reviewmentioning
confidence: 99%